Digestive strategies in two sympatrically occurring lagomorphs - Kuijper, D.P.J; Wieren, S.E. van; Bakker, J.P (Journal of zoology (1987), 2004)
Separation of low digestible fibres and fermentation of the digestible part of the food in the caecum is an adaptation of some small herbivores to cope with low-quality forage. The caecum content is later re-ingested as soft faeces so that the herbivore can benefit from this protein-rich material. This is known as caecotrophy and is a common phenomenon in species of leporids, although differences exist between hares and rabbits. Hares have amorphous soft faeces and the amount of soft faeces produced is smaller compared to that of rabbits. Both factors suggest that hares have smaller benefits from re-ingestion of the caecal contents compared with rabbits and, as a consequence, have a less efficient digestion (mainly of nitrogen) compared to rabbits. The assertion was tested whether digestive efficiency is different between the two herbivores and how this affects the choice of food plants in a natural situation. A feeding trial was conducted using hares and rabbits fed with diets with a range of fibre contents. Dry matter digestibility was not different, but nitrogen digestibility was lower in hares than in rabbits, indicating a less efficient digestion of protein. Both taxa showed a different response to increased fibre content in the diet. Rabbits maximized digestibility by increasing retention time of the food, hares maximized digestion rate by increasing the passage rate of the food through the digestive tract. The daily digestible nitrogen intake was higher in hares Lepus europaeus than that in rabbits Oryctolagus cuniculus, indicating that hares compensated for their lower nitrogen digestibility. Hares were predicted to select for higher quality plant species in a natural situation, but they had, on average, a lower nitrogen and higher total fibre content in their diet compared to sympatrically occurring rabbits. This indicated that hares did not compensate for their lower digestive efficiency by selecting higher quality food plants. The present experiment shows that hares and rabbits have different digestive strategies to cope with low quality forage. Rabbits had a higher N-digestibility by increasing the retention time, whereas hares appeared to compensate for their lower N-digestibility by increasing the processing rate, when food quality deteriorated.